Zwitterion/Brønsted Acid Mixtures Showing Controlled Lower Critical Solution Temperature‐Type Phase Changes with Water. Issue 35 (16th June 2016) - Mieno, Yuki; Kohno, Yuki; Saita, Shohei; Ohno, Hiroyuki
Abstract: A new ammonium‐type zwitterion (ZI), N, N‐ dihexyl‐ N ‐monopentyl‐3‐sulfonyl‐1‐propaneammonium (N665 C3S) with adequate hydrophobicity showed reversible and highly temperature‐sensitive lower critical solution temperature (LCST)‐type phase transitions after being mixed with pure water. Generally for such compounds, those with longer alkyl chains were immiscible with water and those with shorter chains were miscible with water, regardless of temperature. A slightly more hydrophobic ZI than N665 C3S showed LCST‐type phase behavior with water when it was mixed with equimolar amounts of a Brønsted acid such as trifluoromethanesulfonic acid (HTfO). The phase‐transition temperature of the ZI/Brønsted acid mixed aqueous solution was controllable by water content. Abstract : Just a phase ! Ammonium cation‐based zwitterions with adequately designed hydrophobicity were mixed with aqueous Brønsted acid solutions and were shown to reversibly undergo thermoresponsive phase changes between a homogeneous mixture and liquid–liquid phase separation with water by a lower critical solution temperature‐type phase transition (see figure).